al-Ḥarāk al-ṣūfī wa al-daʿwah al-insānīyyah fī Indūnīsīyā: Ḥālah al-Ḥabīb Abī Bakr al-ʿAṭṭās al-Zabīdī - Rijal, Syamsul; Alhabsyi, Musa Alkadzim (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2024)
Studies on Ba'alawi preachers in Indonesia have predominantly focused on popular figures who utilize new media and popular culture in their preaching to appeal to young Muslims. However, there has been a lack of attention given to Ba'alawi preachers who avoid publicity and prioritize humanitarian activities. This article examines the case of Ḥabīb Abū Bakr al-‘Aṭṭās al-Zabīdī (popularly known as Abuya/My Father by his followers), who has garnered a significant following across several Indonesian provinces. His followers regard him as a generous, peace-oriented Sufi who not only advocates for spreading peace and kindness but also embodies these values through humanitarian acts towards those in need, regardless of their religion or ethnicity. This article explores his mobility in business and da'wah across Indonesia and analyzes the methods he uses to distribute charities and empower Muslim communities. The case of Habib Abubakar demonstrates that Sufism transcends mere individual asceticism and detachment from worldly possessions; rather, its spiritual essence is manifested through active involvement in social and humanitarian affairs.